Level of Some Biomarkers of Bone Remodeling in Treated Multiple Myeloma Patients and Compered with New Diagnostic Multiple Myeloma Patients - Shaymaa Obaid Abdullah1 , Hussein Jasim Al-Harbi2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This study was conducted to evaluate the role of some biomarkers of bone remodeling and osteoclast activation/function in treated myeloma patients and to compare results with new diagnostic multiple myeloma(MM) patients who did not receive any treatment . during the period from March (2019) to end November (2019). The study involved measuring serum level of RANKL, Osteoprotegerin (OPG) , RANKL/OPG ratio, Interleukin 6 (IL-6), C-terminal cross-linking telopeptide of type I collagen (CTX type –I) , tartrate-resistant acid phosphatase isoform-5b (TRACP-5b) as markers of bone resorption in 47 treated myeloma patients and the results of these parameters comparing with 13 new diagnosed patients and (30) age- and sex-matched healthy controls groups. The statistical analysis of results showed that the serum level of (RANKL, RANKL/OPG ratio, IL-6, CTX type –I and TRACP-5b) decreased in the treated myeloma patients compared to the new diagnosis patients and the level OPG increased in treated myeloma patients. The results also showed a significant rise (p?0.05) serum level of (RANKL, RANKL/OPG ratio, IL-6, CTX type –I and TRACP-5b) and reduce level OPG in myeloma patients (treated and new diagnosis) in general compared to healthy control individuals . In conclusion, RANKL, OPG and IL-6 play significant roles in MM pathophysiology, as regulators of bone turnover The study showed that an increase leads to an increase in bone resorption, and it appears that chemotherapy reduces resorption .